Mobile application for the control process of childhood anemia in time of the pandemic - Mancisidor-Bazán, Leonel; Morales-Guillén, Isaac; Cabanillas-Carbonell, Michael (International Journal of Public Health Science (IJPHS), 2023)
The objective of the research was to implement a mobile application for the control process of childhood anemia in times of pandemic, in order to have better medical control with faster care, better control of the diagnosis of anemia in children, and better performance and satisfaction. The following Scrum method was applied. The research has a quantitative approach, of experimental type. The sample consisted of 40 children. Results were obtained regarding time control in the speed of care, an increase of 10.2% was obtained; regarding the number of diagnoses, control, and follow-up in recovery there was an increase of 33.3% and finally regarding the control of performance and satisfaction with care there was an increase of 73.3%.